Adaptive Management Practice in the UK Government - The MUVA case - HLS (Human Learning Systems, 2019)
Case study about the MUVA programme in Mozambique. (Maybe it "misses t he point of AP which is not learning for learning. Is learning for imp act. The word impact doesn’t even come up once!") Adaptive Management programming within the Foreign & Commonwealth Development Office demon strates that the UK Government has examples of optimising for learning within its existing management practice. However, currently, the adap tive management practices are unhelpfully framed by an approach which limits both their effectiveness and scope. The programmes use learning as their metastrategy. They succeed in connecting practicebased learn ing with strategic learning, and make a shift towards reframing accoun tability as accountability for learning. This learning strategy is ena bled by funding and contract management arrangements which prioritise learning. Both at macro-level of programme management and micro level of de-risking experimentation and enabling necessary failure by decoup ling people’s job security from potential failure.